Caracterizações óptica e elétrica de cristais de Bi2TeO5 crescidos por um método de duplo cadinho - Fabris, Zanine Vargas (2015)
Bismuth tellurite, Bi2TeO5, here labeled BTeO has a lot of properties like improper ferroelectricity, photochromic, photorefractive, with two optical axes large optical window and another interesting optical and electrical properties, as recently we discovered, photovoltaic effect. BTeO single crystal growth and processing has two inherent difficulties, high vapor pressure of tellurium oxide close to bismuth tellurite melting point and BTeO cleavage plane parallel to (100) plane. So, BTeO factory good sample for material characterization require singular precautions and depends on researcher experience invariably. Present work is dedicated to detailed study of BTeO single crystals growth parameters in a modified Czochralski method with unpublished concept double crucible system. In our case, we used oxides mix on external crucible with volatile oxide bigger quantity related to internal crucible to create a supersaturated atmosphere used to control crystal growth liquid phase stoichiometry reducing tellurium oxide evaporation. We also highlighted important details about good quality samples production, like crystal cut and polish enclosed in acrylic resin to avoid cleavages during this processes. Finally, we characterized BTeO by optical spectroscopy (optical absorption, Raman scattering and luminescence) and electrical properties (conductivity, photoconductivity and impedance spectroscopy). We measured BTeO photorefractive properties with 633 nm wavelength for the first time and results suggested that material could be photovoltaic, hypothesis tested and confirmed in the present work.